Warrior pursuits noble culture and civil conflict in early modern France - Sandberg, Brian 1968- (Johns Hopkins University Studies in historical and political science, 2010)
Prologue -- pt. 1. Profession of arms -- The great quantity of nobility that is found here : Southern France and its warrior elite -- The grandeur and magnificence of his household : noble households and kinship -- He had no helping himself to money : crédit and noble finances -- pt. 2. Bonds of nobility -- With the assistance of my particular friends : clientage and friendship -- The dignity and authority of their charges : officeholding and political culture -- Actions the most perilous being the most honorable : honor and courage -- pt. 3. Culture of revolt -- The call to arms from all quarters : rituals of arming -- A great multitude of soldiers : personal armies -- The zeal of this nobility : violent performances